2011
DOI: 10.1007/s12265-011-9300-4
|View full text |Cite
|
Sign up to set email alerts
|

EMT-Inducing Biomaterials for Heart Valve Engineering: Taking Cues from Developmental Biology

Abstract: Although artificial prostheses for diseased heart valves have been around for several decades, viable heart valve replacements have yet to be developed due to their complicated nature. The majority of research in heart valve replacement technology seeks to improve decellularization techniques for porcine valves or bovine pericardium as an effort to improve current clinically used valves. The drawback of clinically used valves is that they are nonviable and thus do not grow or remodel once implanted inside pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
62
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(64 citation statements)
references
References 124 publications
(109 reference statements)
1
62
1
Order By: Relevance
“…Synthetic polymers have the advantage in that they have predictable chemistry and their properties can be well-controlled [2]. Additionally, these materials are FDA (Food and Drug Administration) regulated and many have been approved in clinical applications [46]. The most commonly utilized synthetic polymers in tissue engineering include poly(glycolic acid) (PGA), poly(L-lactic acid) (PLLA), copolymer poly(lactic-co-glycolic acid) (PLGA), poly(ethylene glycol) (PEG), and polyhydroxyalkanoate (PHA).…”
Section: Chapter 40 Tissue-engineering Heart Valvesmentioning
confidence: 99%
See 2 more Smart Citations
“…Synthetic polymers have the advantage in that they have predictable chemistry and their properties can be well-controlled [2]. Additionally, these materials are FDA (Food and Drug Administration) regulated and many have been approved in clinical applications [46]. The most commonly utilized synthetic polymers in tissue engineering include poly(glycolic acid) (PGA), poly(L-lactic acid) (PLLA), copolymer poly(lactic-co-glycolic acid) (PLGA), poly(ethylene glycol) (PEG), and polyhydroxyalkanoate (PHA).…”
Section: Chapter 40 Tissue-engineering Heart Valvesmentioning
confidence: 99%
“…It has been used as an autogeneic scaffold in heart valve tissue engineering [52]. Some advantages of using fibrin gel as a material for scaffold construction include that it is made from the patient's own blood, and also that it is readily Overview of tissue engineering heart valves [46].…”
Section: Chapter 40 Tissue-engineering Heart Valvesmentioning
confidence: 99%
See 1 more Smart Citation
“…[63][64][65] bFGF plus EGF can trigger Wnt signaling pathway to induce epithelial-mesenchymal transition, which is an important process in the embryonic development of the heart valve. 66,67 The combination of bFGF and EGF can also maintain fibroblastic phenotype by inhibiting TGF-b-induced activation 68 and preserving multipotential properties of ovine BMMSC. 69 In addition, Song et al and Biver et al found that FGF2 could inhibit bone morphogenic protein-induced osteogenic differentiation of MSC.…”
mentioning
confidence: 99%
“…Critical valvular heart disease is a serious cardiovascular complication 38 . In infants, congenital heart defects occur in four to six infants for every 1000 births 39 .…”
Section: Introductionmentioning
confidence: 99%